Oral probiotic VSL#3 attenuates the circulatory disturbances of patients with cirrhosis and ascites. (4th April 2014) - Rincón, Diego; Vaquero, Javier; Hernando, Ana; Galindo, Evelyn; Ripoll, Cristina; Puerto, Marta; Salcedo, Magdalena; Francés, Rubén; Matilla, Ana; Catalina, María V.; Clemente, Gerardo; Such, José; et al.
Abstract Background & Aims The modulation of gut flora constitutes a therapeutic tool in patients with liver disease, but some of its modalities require further investigation. Here, we evaluated the effects of probiotics on the hepatic and systemic haemodynamic alterations of advanced liver disease. Methods Seventeen patients with cirrhosis and ascites were prospectively included, five of whom abandoned this study prematurely. Hepatic and systemic haemodynamic evaluations were performed at baseline and after 6 weeks of receiving an oral VSL#3 probiotic preparation. Peripheral blood analyses included the evaluation of cytokines (TNF‐alpha, IL‐1beta, IL‐6), bacterial translocation [bacterial DNA and lipopolysaccharide‐binding protein (LBP)] and nitric oxide end‐products (NOx). Results In 12 patients completing this study, the oral administration of VSL#3 resulted in reductions of the hepatic venous pressure gradient (HVPG, P < 0.001), cardiac index and heart rate (both P < 0.01) and in increases of the systemic vascular resistance (P < 0.05) and mean arterial pressure (P = 0.06). HVPG decreased at least 10% from baseline in eight patients (67%). Serum sodium increased in most patients (P < 0.01). All these changes were unrelated to the detection of bacterial DNA or to the levels of LBP, pro‐inflammatory cytokines or NOx. No significant adverse effects were observed. Conclusion Administration of the probiotic mixture VSL#3 improved the hepatic and systemic haemodynamics and serum sodium levels in patients with cirrhosis. Our results identify major effects of probiotics in liver disease and provide the rationale for assessing their therapeutic potential against the progression of portal hypertension and its complications in future clinical trials.